Philippines social development perspectives do people really matter? - Buendia, Rizal G. (Philippine Journal of Public Administration, 1995)
Social development, in its broadest sense, is human development. Social development policies have been articulated by the government in several national programs - medium-term Philippine development Plan, Social Reform Agenda, and Human Development Report. However, these programs still fall short of addressing the real concerns of human development. Among the issues that remain to be resolved are, among other: allocation of funds to social development programs; reliable and valid source of information and data regarding the target clientele; and realistic indicators of empowerment.